Modelling and Simulation of Electrical Energy Systems through a Complex Systems Approach using Agent-Based Models - Kremers, Enrique Alberto (KIT Scientific Publishing, 2013)
Complexity science aims to better understand the processes of both natural and man-made systems which are composed of many interacting entities at different scales. A disaggregated approach is proposed for simulating electricity systems, by using agent-based models coupled to continuous ones. The approach can help in acquiring a better understanding of the operation of the system itself, e.g. on emergent phenomena or scale effects; as well as in the improvement and design of future smart grids.